Modificações estruturais e funcionais da folha de Eremanthus Incanus (less.) Less. (Asteraceae) em diferentes ambientes no parque ecológico quedas do Rio Bonito - Silva, Elias Roma da (2018)
The vegetation of the Alto Rio Grande is composed of forest patches, cerrado and rock field. This remarkable physiognomic variation is due to the reason for this region to shelter one of the transition areas between the cerrado of central Brazil and the semideciduous forests of th e southeast and south of the country. Eremanthus incanus (Asteracaeae) is one of many species that occurs in these different environments, indicating a probable plasticity to fit the environmental variations of these phytophysiognomies.. The objective of this study was to analyze the anatomical and physiological modifications of leaves of E. incanus, in different vegetation physiognomies. For this, the leaves of ten individuals from three different areas were collected: 1) Mata - Cerrado transition; 2) Rocky Field and 3) Closed Transition - Rocky Field. The slides of transversal and paradermica sections were stained and photographed. Data were also obtained in the field of gas exchange using IRGA, SPAD and MINI-PAM. From a principal component analysis, the anatomical and physiological variables that obtained the highest significance value were selected, and a multivariate regression analysis was performed using the three environments (explanatory variable) and the anatomical and physiological variables (response variables). Thus, the effect of the explanatory variable on the response variables was evaluated using analysis of variance and Chi-square test (p <0.05). A qualitative analysis of the leaf anatomy of E. incanus revealed uniseriate epidermis, dorsiventral mesophyll, amphistomatic leaves and a large number of trichomes on the abaxial surface. The thickness of the adaxial epidermis and the amount of abaxial trichomes were altered due to the environmental variations of each area. In the Closed - Field Transition area, the leaves of E. incanus showed a greater thickness of the adaxial epidermis and of the trichomes region, probably due to the fact that this area contains little water availability in the soil and is exposed to constant solar radiation causing an increase in leaf temperature. Thus, the structural modifications favored a greater assimilation of CO 2 , greater efficiency in water use, and less transpiration of the E. incanus leaves. This result shows that this species has a plasticity to adapt to different environments and their environmental variations.